(untitled) (The International Journal for Scientific Research, 2024)
The desert represents a profound textual space in the writings of the Omani poet, Saif Al Rahbi. His texts emanate broadly from an ancient Arabian memory laden with rich emotional and cultural contents, and, more specifically, from the land to which he belongs, the Arabian Peninsula, of which the desert is a significant component. The dominant presence of the desert in his poems is expressed through a glossary of terms that convey rigidity and harshness, on the one hand, and nostalgia, crumbling and passion, on the other hand. The imposing presence in Arabic literature of this Omani poet, with origins deeply rooted in the desert and its quick sands, is owed to his unique poetic style. Various linguistic formulations and visual contradictions, combined with the poet’s internal rhythm of emotions, create composites of personal visions that coalesce to furnish the text with endless structural, decorative, visual and mental possibilities, paving the way for a connection between the text and its reader. As for the forest, its cruel presence in the text is felt mainly through its various wild creatures. This study is an attempt to trace the image of the desert and the forest in Saif Al Rahbi’s poetry by identifying its distinct linguistic properties and artistic formulations.